2020
DOI: 10.1038/s41467-020-15490-8
|View full text |Cite
|
Sign up to set email alerts
|

Essential dynamic interdependence of FtsZ and SepF for Z-ring and septum formation in Corynebacterium glutamicum

Abstract: The mechanisms of Z-ring assembly and regulation in bacteria are poorly understood, particularly in non-model organisms. Actinobacteria, a large bacterial phylum that includes the pathogen Mycobacterium tuberculosis, lack the canonical FtsZ-membrane anchors and Z-ring regulators described for E. coli. Here we investigate the physiological function of Corynebacterium glutamicum SepF, the only cell division-associated protein from Actinobacteria known to interact with the conserved C-terminal tail of FtsZ. We sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 82 publications
8
70
0
Order By: Relevance
“…For ectopic expression in C. glutamicum , the pbp2m gene was amplified from C. diphtheriae strain FRC0402 and put under the control of the inducible P gntK promoter on the shuttle vector pTGR5 [ 58 ] (Additional file 4 : Fig. S1) .…”
Section: Methodsmentioning
confidence: 99%
“…For ectopic expression in C. glutamicum , the pbp2m gene was amplified from C. diphtheriae strain FRC0402 and put under the control of the inducible P gntK promoter on the shuttle vector pTGR5 [ 58 ] (Additional file 4 : Fig. S1) .…”
Section: Methodsmentioning
confidence: 99%
“…In B. subtilis , SepF is non-essential and has an overlapping role with FtsA, as overexpression of SepF can rescue an FtsA depletion strain 16 , 17 . In contrast, in other bacterial lineages where FtsA is absent, such as most Actinobacteria and Cyanobacteria , SepF is an essential component of the early divisome, orchestrating Z-ring assembly and participating in membrane remodeling 18 21 . The first crystal structure of a bacterial SepF-FtsZ complex was only recently obtained from the Actinobacterium Corynebacterium glutamicum 21 .…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, in other bacterial lineages where FtsA is absent, such as most Actinobacteria and Cyanobacteria , SepF is an essential component of the early divisome, orchestrating Z-ring assembly and participating in membrane remodeling 18 21 . The first crystal structure of a bacterial SepF-FtsZ complex was only recently obtained from the Actinobacterium Corynebacterium glutamicum 21 . It showed that SepF forms a functional dimer that is required for FtsZ binding 21 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations